Drinking Behavior. The Icelandic Economic Crisis and Recovery - Ásgerður Theodóra Björnsdóttir 1959- (2016)
Alcohol consumption, in particular excessive alcohol consumption, imposes high costs on societies through consequences, such as lost productivity, early mortality, health-care costs, car accidents and crime. The main objective of this study is to examine how drinking behavior developed over an economic boom, subsequent crisis, and an eventual recovery. We use individual longitudinal data collected through a postal survey by The Directorate of Health in Iceland in 2007, 2009 and 2012. Pooled OLS and linear probability models are used to study four outcomes: Alcohol-consumption frequency, frequency of binge drinking, binge-drinking participation and alcohol dependence. Alcohol-consumption frequency declined during the crisis, with a further decline during the recovery period. This change is driven by female behavior between 2007 and 2009, but a combined gender effect between 2009 and 2012. This effect is suppressed by male labor-market-changes, but partly mediated by labor marked changes in the case of females. Alcohol dependence declined during the crisis, with suggestive evidence of partially reverting back to previous levels during the recovery. There is some indication that during the crisis real price changes of alcohol played a role in the decline in alcohol consumption but that is not a likely determinant of changes in alcohol consumption for the three year period post-crisis that we explore. Men’s consumption can partly be explained through income changes while women’s consumption changes are rather driven by changes in work hours or other factors. Neysla áfengis, einkum óhófleg neysla áfengis, er samfélögum kostnaðarsamt vandamál vegna afleiðinga eins og ótímabærra andláta, skertrar framleiðni, aukins heilbrigðiskostnaðar, bílslysa og glæpa. Meginmarkmið þessarar rannsóknar er að skoða hvernig efnahagsleg uppsveifla, hrun og efnahagslegur bati hefur áhrif á áfengisdrykkju. Notuð voru einstaklingsbundin langsniðsgögn úr spurningalistarannsókn Embættis landlæknis; Heilsa og líðan Íslendinga fyrir árin ...